2016
DOI: 10.1097/cad.0000000000000318
|View full text |Cite
|
Sign up to set email alerts
|

Oroxin A inhibits breast cancer cell growth by inducing robust endoplasmic reticulum stress and senescence

Abstract: Breast cancer is a major cause of cancer death among women. Although various anticancer drugs have been used in clinics, drugs that are effective against advanced and metastatic breast cancer are still lacking and in great demand. In this study, we found that oroxin A, an active component isolated from the herb Oroxylum indicum (L.) Kurz, effectively inhibited the growth of human breast cancer cells MDA-MB-231 and MCF7 by inducing endoplasmic reticulum (ER) stress-mediated senescence. Oroxin A caused breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…TSA-induced apoptosis is an important function for cancer therapy; p53 has been identified to influence the antitumor effect of TSA (4). Tumor cells experience constant ER stress and are exposed to various stress stimuli in their microenvironment, including the accumulation of misfolded proteins, hypoxia, acidic pH levels, reactive oxygen species, calcium imbalance, viral proteins and hypoglycemia (23). Therefore, substantial ER stress may easily be induced in tumor cells, which may lead to tumor cell death.…”
Section: Discussionmentioning
confidence: 99%
“…TSA-induced apoptosis is an important function for cancer therapy; p53 has been identified to influence the antitumor effect of TSA (4). Tumor cells experience constant ER stress and are exposed to various stress stimuli in their microenvironment, including the accumulation of misfolded proteins, hypoxia, acidic pH levels, reactive oxygen species, calcium imbalance, viral proteins and hypoglycemia (23). Therefore, substantial ER stress may easily be induced in tumor cells, which may lead to tumor cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Oroxin A (OA, baicalein-7-O-glucoside, Figure 1A) is one of the active ingredients isolated from the traditional herbal medi- cine Oroxylum indicum (L.) Kurz of Asian countries [23,24]. Accumulating studies have shown the beneficial biological effects of OA, which include antioxidant, antidiabetic, anticancer, antibacterial, anti-inflammatory and antiviral properties [25][26][27][28][29][30]. Herein, we selected Q [8] as a host molecule and investigated its host-guest interactions with OA, as well as its effect on the properties of OA.…”
Section: Introductionmentioning
confidence: 99%
“…ER stress plays an important role in polyphenol-mediated cell senescence (Figures 3 and 4). An active flavonoid component oroxin A, which is obtained from the traditional Chinese herb Oroxylum indicum (L.) Kurz, increased ER-Tracker Red-positive cell population and upregulated ER stress-related proteins activating transcription factor 4 (ATF4) and binding immunoglobulin protein (GRP78), caused cell cycle arrest at the G2/M phase and induced senescence in human breast cancer cells while p38-specific inhibitor SB203580 blocked ER stress induced senescence [79]. Cristacarpin, a known isoflavonoid isolated from Erythrina suberosa stem bark, enhanced ER stress with increased expressions of GRP-94 and PERK by activation of p38, thereby generating sub-lethal ROS, elevating the expression of p21 waf1 in a p53-independent manner, and reducing the expressions of Cdk-2 and cyclinD1, which in turn caused cellular senescence through G1 phase cell cycle arrest in pancreatic and breast cancer cells [80].…”
Section: Endoplasmic Reticulum (Er) Stress-induced Senescencementioning
confidence: 99%